Designing Software Management Work Unit of Research and Development Department of Public Works and Public Housing - Suryana, Ase; Supendi, Yiyi; Yulianto, Erwin (International Journal of Advanced Science and Technology, 2019)
Currently the management of the Work Unit in the Research and Development Center of the Ministry of Public Works and Public Housing is still using a simple computerized system, even though it has been supported by a computer. This causes several obstacles including supervision and control of the workings of each work unit in the Research and Development Center which is still slow which results in errors in processing transaction data. This software design uses descriptive research methods with the type of case study research at the Research and Development Center of the Department of Public Works and Public Housing with data collection techniques used are observation, interviews, and literature studies. The data analysis technique uses an incremental model developed from the waterfall model, while the analysis model uses structured design analysis. Software System design is a Web base with MySql database. Data processed in this system include official travel transaction data, data on procurement of goods, payment transaction data for expert salaries, procurement of rental services and procurement of consultancy services including the use of annual budget. System testing conducted consists of alpha testing using black box testing methods. The conclusion of the test results states that the application is quite interesting, easy to use, helps in processing data, and can provide the desired information.